Projected changes in temperature, precipitation, and their extremes over China through the RegCM - Lu, Chen; Huang, Guohe; Wang, Xiuquan (Climate dynamics, 2019)
As the second biggest economy in the world, China has been experiencing significant impacts of global climate change. Developing future projections of regional climate over China is an indispensable step for designing appropriate mitigation and adaptation strategies against future climate change. To this end, this study focuses on exploring how the regional climate over China, including the mean and extreme climate, will be affected in the context of global warming throughout this century. The RegCM model is used to develop high-resolution climate scenarios for the whole country of China driven by boundary conditions of the Geophysical Fluid Dynamics Laboratory (GFDL) model under the Representative Concentration Pathways (RCPs). RegCM performance on simulating the present climate over China is evaluated and the results indicate that it is capable of reproducing the spatial distributions of temperature and precipitation. Future projections from RegCM suggest that an increase of 2 °C in daily mean temperature is expected in China by the end of the twenty-first century under RCP4.5 while an increase of 4 °C would be seen under RCP8.5. The Tibetan Plateau is likely to expect the most substantial temperature increase as well as the most significant decrease in extreme cold climate in China. In comparison, the annual total precipitation over China is projected to increase by 58 mm/year at the end of the twenty-first century under RCP4.5 and by 71 mm/year under RCP8.5. The projected changes in precipitation show apparent spatial variability due to the influences of local topography and land cover/use.